Dynamics of P-M hybrid dysgenesis in P-transformed lines of Drosophila simulans. - Montchamp-Moreau, C. (Evolution, 1990)
An autonomous P element from Drosophila melanogaster was introduced by microinjection into the germ line of its sibling species, Drosophila simulans. The invasion kinetics of P elements was studied in seven independent lines over 60 generations, using gel blotting, in situ hybridization, and dysgenic crosses. Some of the main phenotypic and molecular characteristics of P-M hybrid dysgenesis were observed, i.e., gonadal dysgenesis (GD sterility), chromosome rearrangements, and the occurrence of degenerate P elements. At least four lines reached a steady state with complete or nearly complete P-element regulation but with a moderate number of P elements (10-24 per haploid genome) and P activity (10-35% GD sterility). This failure to obtain strong P strains in D. simulans could be due to experimental conditions, a host-dependent component of P transposition, or more severe selection against the deleterious effects of this transposon.